2013
DOI: 10.1038/hdy.2013.5
|View full text |Cite
|
Sign up to set email alerts
|

Natural variation of the Y chromosome suppresses sex ratio distortion and modulates testis-specific gene expression in Drosophila simulans

Abstract: X-linked sex-ratio distorters that disrupt spermatogenesis can cause a deficiency in functional Y-bearing sperm and a femalebiased sex ratio. Y-linked modifiers that restore a normal sex ratio might be abundant and favored when a X-linked distorter is present. Here we investigated natural variation of Y-linked suppressors of sex-ratio in the Winters systems and the ability of these chromosomes to modulate gene expression in Drosophila simulans. Seventy-eight Y chromosomes of worldwide origin were assayed for t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
38
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 37 publications
(41 citation statements)
references
References 68 publications
3
38
0
Order By: Relevance
“…Moreover, analyses of Y chromosome variation in wild-type backgrounds and in genotypes with loss-of-function mutations revealed that the manifestation of YRV is exquisitely sensitive to the genomic background (Jiang et al, 2010;Branco et al, 2013a, b). Moreover, these studies support the expectation that Y-linked variation preferentially affects genes with male-biased expression and modifies male fertility.…”
Section: Introductionsupporting
confidence: 63%
See 4 more Smart Citations
“…Moreover, analyses of Y chromosome variation in wild-type backgrounds and in genotypes with loss-of-function mutations revealed that the manifestation of YRV is exquisitely sensitive to the genomic background (Jiang et al, 2010;Branco et al, 2013a, b). Moreover, these studies support the expectation that Y-linked variation preferentially affects genes with male-biased expression and modifies male fertility.…”
Section: Introductionsupporting
confidence: 63%
“…These data suggest that the genotype Dox/nmy (Dox distorter/nmy lack-offunction suppressor) has a predominant effect on fertility regardless of the Y chromosome. Interestingly, Branco et al (2013a) have shown that the D. simulans Y chromosome is polymorphic for its capacity to modulate sex ratio distortion in genotype SR12-2-7. These authors used the same stock SR12-2-7 as a background for the introgression of 78 Y chromosomes from several D. simulans populations and found that there is significant diversity in Y chromosome resistance to sexratio distortion: some Y chromosomes carry YRV that overrides the effects of the distorter Dox, while other Y chromosomes are even more sensitive to Dox than the original Y chromosome present in SR12-2-7.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations